2016
DOI: 10.1016/j.jaci.2015.12.782
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Exacerbated Respiratory Disease Involves a Cysteinyl Leukotriene-Driven IL-33-Mediated Mast Cell Activation Pathway

Abstract: Aspirin exacerbated respiratory disease (AERD), a severe eosinophilic inflammatory disorder of the airways, involves overproduction of cysteinyl leukotrienes (cysLTs), activation of airway mast cells (MCs), and bronchoconstriction in response to nonselective cyclooxygenase inhibitors that deplete homeostatic prostaglandin (PG)E 2 . The mechanistic basis for MC activation in this disorder is unknown. We now demonstrate that patients with AERD have markedly increased epithelial expression of the alarmin-like cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 39 publications
1
40
2
3
Order By: Relevance
“…Expression of LTC 4 S in eosinophils drives much of the over-production of CysLTs 24 with additional components driven by the activation of mast cells 3, 5, 26, 27 and platelet-adherent neutrophils 28 . While contributing to many of the untoward effects of AERD, as evinced by the beneficial effects of leukotriene modifiers 29 , increasing attention has been given to contributions from PGD 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Expression of LTC 4 S in eosinophils drives much of the over-production of CysLTs 24 with additional components driven by the activation of mast cells 3, 5, 26, 27 and platelet-adherent neutrophils 28 . While contributing to many of the untoward effects of AERD, as evinced by the beneficial effects of leukotriene modifiers 29 , increasing attention has been given to contributions from PGD 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lung tissue lysates from PGE synthase −/− NERD-like mice showed that IL-33 is responsible from mast cell activation after a challenge with lysine-aspirin and LTE 4 is responsible for IL-33-dependent mast cell activation and airflow obstruction. 27 In a case series involving three children and adolescents with NERD, 24-hours urinary levels of prostaglandin D2, histamine, and 11β prostaglandin F2α, as well as serum IL-5 and IL-13 levels, are increased. 28 Additionally, mild baseline eicosanoid imbalance is detected in three adolescents aged 17 (2 of them) and 13 years using in vitro functional eicosanoid test.…”
Section: Mechanis Ms Of N Said Hyper S En S Itivit Ymentioning
confidence: 98%
“…Western blots of whole nasal polyp lysates from patients with NERD and lung tissue lysates from PGE synthase −/− NERD‐like mice reveal high interleukin‐33 (IL‐33) expression compared to controls without NERD. Furthermore, lung tissue lysates from PGE synthase −/− NERD‐like mice showed that IL‐33 is responsible from mast cell activation after a challenge with lysine‐aspirin and LTE 4 is responsible for IL‐33–dependent mast cell activation and airflow obstruction . In a case series involving three children and adolescents with NERD, 24‐hours urinary levels of prostaglandin D2, histamine, and 11β prostaglandin F2α, as well as serum IL‐5 and IL‐13 levels, are increased .…”
Section: Mechanisms Of Nsaid Hypersensitivitymentioning
confidence: 99%
“…Likewise, studies have demonstrated decreased production of anti‐inflammatory prostaglandin E 2 (PGE 2 ) and reduced expression of COX‐2, an enzyme important in PGE 2 synthesis in nasal polyp tissue from patients with AERD . These alterations in arachidonic acid metabolism are associated with increased mast cell activation and eosinophilic inflammation of the upper and lower airways …”
Section: Review Characteristicsmentioning
confidence: 99%